Influence of three different implant thread designs on stress distribution: A three-dimensional finite element analysis - Mansi Manish Oswal; Ulhas N Amasi; Manish S Oswal; Ashish S Bhagat (Wolters Kluwer Medknow Publications, 2016)
Purpose: Clinical success of implant prosthodontics is dependent in part upon the type of implant thread design. The selection of implant thread design plays an important role in the outcome of the treatment. This study was undertaken to evaluate the pattern of stress distribution using a finite element analysis; hence, the area which would be bearing maximum load for a given design would be arrived. Materials and Methods: Three implants with different thread designs, namely V-thread, buttress, and reverse buttress thread designs were considered and dimensions were standardized. The site considered was the mandibular molar region with cortical and trabecular bone assuming to be isotropic and homogeneous. The implant modeling was done with the CATIA software. Vertical loads of 100N were applied. The stresses were calculated as Von Mises stress criterion. Results: Maximum stresses were seen at the cortical bone and were transferred to the implant. Minimum Von Mises stresses were seen with reverse buttress thread design at the cortical bone. The stresses were observed least at the cancellous bone and maximum at the implant. Conclusion: Hence, within the limitations of this study the results obtained can be applied clinically for appropriate selection of implant thread design for a predictable success of implant therapy.